Relationship Between Hypertension and Sleep: An Overview: Life Sciences-Medicine - Omar Asraf, Nisreen; Hasan Mohammad Kailani, Abdulrahman; Ahmad Altawili, Mohammed; Burayk Almutairi, Mohammed; Sahl Zolali, Hamza; Mujir Aljahdali, Salma; Shroq Hassan S, Alzahrani; Abdullah A Bonais, Norah; Abdulelah R Alotaibi, Turki; Shahid Ahmed, Rida; Othman Malayoo, Baraah; Yaser Al Abbas, Zahra; et al. (International Journal of Life Science and Pharma Research, 2022)
Abstract: Sleep is a necessary component of the human lifestyle. A growing number of studies have focused on the relationship between sleep and hypertension in recent years. Sleep health plays a role in the pathophysiology of hypertension, but because of the complexity of the relationship, it can be challenging to pinpoint specific sleep abnormalities linked to blood pressure elevation at the epidemiological level as well as the level of a given patient. According to the available evidence, poor sleep conditions may be an important risk factor in the pathophysiological abnormalities of hypertension and related comorbid states. According to ambulatory blood pressure studies, even minor increases in blood pressure, particularly at night, are associated with significant increases in cardiovascular morbidity and mortality. As a result, sleep-related diseases that cause blood pressure increases are expected to impact cardiovascular risk significantly. Insomnia and sleep deprivation have been linked to an increase in the incidence and prevalence of hypertension. Sleep influences autonomic nervous system function and other physiologic events that affect blood pressure. Although current evidence suggests a strong link between sleep duration and hypertension, the relationship between sleep quality and hypertension needs to be investigated further. Unfortunately, the regularity and underlying mechanism of sex differences in sleep quality and hypertension remain unknown due to differences in geography, population, confounding factors, or methods. The current evidence suggests that the link between poor sleep quality and hypertension is stronger in women than in men. Furthermore, sleep disorders alter the BP response and raise the risk of hypertension. Recent research on the effects of sleep and sleep disorders on blood pressure and hypertension will be examined.